Kepatuhan Pajak Individu: Sosialisasi Perpajakan, Tax Morale, Ketegasan Sanksi Pajak - Febriyanti, Ni Kadek Ayu; Indraswarawati , Sang Ayu Putu Arie; Muliati, Ni Ketut (Hita Akuntansi dan Keuangan, 2025)
Compliance with taxation is affectes by internal as well ass external factors. Proper dissemination of tax information, high moral responsibillity in taxation, and firm application of sanction are consideres to improve compliance especially among personal taxpayers. This study aims to asses the influence of tax socialitation, tax morale and strict enforcement of sanctions on taxpayer compliance at the West Denpasar Tax Office.  The study applied a survey method by handing out questionaires to 100 participants selected through a simple random sampling procedure. The data obtained were analyzed using the multiple linear regression method. The findings revealed tha the three independent variables had a significant positive impact on individual taxpayer compliance. The results emphasize that strengthening tax socialization, improving tax morale, and maintaining consistent sanction enforcement are key strategies to boost taxpayer compliance.